PERSEPSI MAHASISWA TERHADAP KEBERADAAN SUMBER BELAJAR (Studi Kasus di Sekolah Tinggi Penyuluhan Pertanian (STPP) Magelang Jurusan Penyuluhan Pertanian Yogyakarta) - Arifin, Miftakhul (Jurnal Ilmu-Ilmu Pertanian, 2015)
This study aims to determine the existence, degree of utilization, the level of needs and interests, and the level of service-learning resources in the Department of Agricultural Extension STPP Magelang in Yogyakarta. This research is quantitative descriptive. Object of this research is a source of learning, and the respondents are students in the Department of Agricultural Extension STPP Magelang in Yogyakarta. Data were collected using questionnaires, then analysed descriptively. The results showed (1) The existence of Learning Resources i.e. Massage, People, Engineering, and Environment have always existed categories, while Materials and Equipment have occasionally their categories. Quality of Learning Resources i.e. People and Environment have very adequate category, while other forms adequate categories. (2) Utilization rate which includes the user number and frequency of use of Learning Resources i.e. Messages, Person, Engineering and Environment have a lot of and often categories, while Materials and Equipment have the medium and sometimes categories. (3) The level purposes of all forms of Learning Resources have very necessary categories. (4) The level of pleasure almost all forms of Learning Resources have very favoured categories, except the form of Equipment. (5) The level of service that includes Speed and Ease of Service almost all have quick and easy categories. Results of this study have implications for the future development of learning resources that exist in Department of Agricultural Extension STPP Magelang in Yogyakarta.